Paracardial lipodystrophy versus pericardial effusion in HIV positive patients. Issue 5 (1st May 2002) - Neumann, T; Chanbay, A; Barkhausen, J; Bartel, T
Abstract : Objective: To present an epicardial manifestation of the lipodystrophy syndrome, a side effect of antiretroviral treatment in HIV positive patients, which illustrates the important danger of false diagnosis. Patient: A 52 year old man with HIV (stage C3), diagnosed 10 years previously, was being treated with a combination of nelfinavir, nevirapine, and stavudine. Echocardiographic examination showed a low echogenic pericardial space that had increased from 4 mm to 18 mm over a 10 month period. The diagnosis of paracardial adipose tissue was verified by magnetic resonance tomography. Doppler echocardiographic parameters were not significantly altered (ratio of early to late ventricular filling 0.88 v 0.73, Tei index 0.30 v 0.36). Conclusion: Even a pericardial manifestation of lipodystrophy causes negligible functional impairment, misinterpretation of the lipodystrophy as a pericardial effusion and a subsequent puncture can have serious complications. Hence, it is strongly suggested that further differential diagnosis be used for HIV positive patients with an echocardiographic suspicion of pericardial effusion. Differential diagnosis by magnetic resonance tomography is possible.